City Branding Shining Batu dan E-WOM serta Pengaruhnya terhadap Niat Berkunjung Wisatawan (Studi pada Wisatawan di Kota Batu) - Shelea Aleonita; Anik Lestari Andjarwati (Jurnal Ilmu Manajemen, 2020)
The purpose of this paper was to study the relationships among city branding, e-WOM (electronic word of mouth), and tourists intention for visiting. The study focused on the tourists who would visit Batu City as the sample by using a nonprobability sampling technique. Questionnaires were distributed to 200 participants by google forms. Data analysis techniques were Multiple Linear Regression with validity and reliability test, classic assumption, and hypothesis test (t-test). The results indicated that city branding is positively influenced by the tourists intention for visiting, but e-WOM is negatively influenced by the tourists intention for visiting. The implications in this study can be used as input for the Batu City Government in developing the city branding œShining Batu to increase tourists intention for visiting.